1998
DOI: 10.1016/s1097-2765(00)80152-5
|View full text |Cite
|
Sign up to set email alerts
|

The Heterochromatin Protein 1 Prevents Telomere Fusions in Drosophila

Abstract: HP1 (Heterochromatin protein 1) is a conserved, non-histone chromosomal protein that is best known for its preferential binding to pericentric heterochromatin and its role in position effect variegation in Drosophila. Using immunolocalization, we show that HP1 is a constant feature of the telomeres of interphase polytene and mitotic chromosomes. This localization does not require the presence of telomeric retrotransposons, since HP1 is also detected at the ends of terminally deleted chromosomes that lack these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
291
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(305 citation statements)
references
References 54 publications
12
291
2
Order By: Relevance
“…Several observations, however, indicate that the contribution of WOC/ROW/HP1c is not related to that of HP1a. On one hand, su(var)2-5 mutants show much stronger effects than either woc or row mutants (Fanti et al 1998;Raffa et al 2005). Furthermore, both telomere length and expression of the telomeric retrotransposons Het-A and TART are increased in su-(var)2-5 mutants, but they are not affected in woc-null mutants (Perrini et al 2004;Raffa et al 2005).…”
Section: Hp1c and Telomere Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several observations, however, indicate that the contribution of WOC/ROW/HP1c is not related to that of HP1a. On one hand, su(var)2-5 mutants show much stronger effects than either woc or row mutants (Fanti et al 1998;Raffa et al 2005). Furthermore, both telomere length and expression of the telomeric retrotransposons Het-A and TART are increased in su-(var)2-5 mutants, but they are not affected in woc-null mutants (Perrini et al 2004;Raffa et al 2005).…”
Section: Hp1c and Telomere Functionmentioning
confidence: 97%
“…HP1a is also known to regulate telomere function (Fanti et al 1998). Several observations, however, indicate that the contribution of WOC/ROW/HP1c is not related to that of HP1a.…”
Section: Hp1c and Telomere Functionmentioning
confidence: 99%
“…Nevertheless, the phenotypes of HP1 mutants indicate that if such interactions do occur, they are not critical for Nipped-B and cohesin function. It has been reported that polytene chromosomes appear relatively normal in HP1 [Su(var)2-5] mutants and cohesion defects do not occur in any of the several tissues examined (Fanti et al 1998). Polytene chromosomes that lack cohesin, on the other hand, show a significant change in morphology (Dorsett et al 2005).…”
Section: Nipped-b Cohesin and Pds5 Colocalize On Salivary Polytene mentioning
confidence: 97%
“…Telomeres are heterochromatic regions. Yeast and flies with defects in activities that modify the state of chromatin also have abnormal telomere function [4][5][6] , but the putative role of chromatin-modifying activities in regulating telomeres in mammals is unknown. Here we report on telomere length and function in mice null with respect to both the histone methyltransferases (HMTases) Suv39h1 and Suv39h2 (called SUV39DN mice).…”
mentioning
confidence: 99%
“…Heterochromatic regions are enriched in methylated H3-Lys9, which creates a binding site for the chromobox proteins 9 , mediators of heterochromatin formation and epigenetic gene regulation. In D. melanogaster, HP1 is also required for telomere capping 4,5 . To investigate the impact of H3-Lys9 methylation on telomere length regulation and telomere function, we studied embryonic stem (ES) cells and mouse embryonic fibroblasts (MEFs) from SUV39DN mice 7 , which have less methylation of H3-Lys9 at the pericentric heterochromatin compared to wildtype mice 7 .…”
mentioning
confidence: 99%